SIKAP DAN KEPUASAN KONSUMEN TERHADAP MINUMAN KOPI DI WARKOP WAW DI KOTA BANDAR LAMPUNG - Sunarya, Onah; Endaryanto, Teguh; Nugraha, Adia (Indonesian Journal of Socio Economics, 2023)
The purpose of this study were to determine the characteristics of consumers towards purchasing Waw coffee drinks at Warkop Waw in Bandar Lampung City, to know consumer attitudes towards purchasing Waw coffee drinks at Warkop Waw in Bandar Lampung City, and to know the level of customer satisfaction with purchasing Waw coffee drinks at Warkop. Waw in the city of Bandar Lampung. The method used in this research was a survey method. The research was conducted at Warkop Waw, Bandar Lampung City. The location selection was carried out purposively with the consideration that Warkop Waw is a coffee place that not only serving delicious coffee to drink but also has many health benefits. Data analysis used in this research was descriptive analysis, validity and reliability test, Fishbein multi-attribute analysis, Customer Satisfaction Index (CSI), Importance and Performance Analysis (IPA). The results of the analysis of consumer attitudes using the Fishbein multi-attribute model at Waw coffee drinks in Warkop Waw, Bandar Lampung City showed that the efficacy attribute got the highest attitude score and the display attribute got the lowest score. The level of customer satisfaction based on the Customer Satisfaction Index (CSI) analysis was 83.44%, which means that consumers are satisfied with the performance of Waw coffee drinks in Warkop Waw, Bandar Lampung City.